Comparative analysis of transabdominal preperitoneal and total extraperitoneal plastic surgeries in inguinal hernia repair - A. S. Savin; A. V. Khokhlov; D. V. Dvoryankin (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. Comparative analysis of transabdominal preperitoneal (TAPP) and total extraperitoneal (TEP) plastic surgeries was made in case of inguinal hernia repair. MATERIAL AND METHODS. Patients (n =236) underwent surgery at the period from 2012 till 2016. The TAPP was performed in 114 (48,3 %) patients and TEP was carried out in 122 (51,7 %). Clinical analysis of results was made in two groups. RESULTS. The research didn’t show any significant difference in the rate of intra- and postoperative complications and recurrences, but their structure varied. However, length of operation was less in case of one-sided hernia in TAPP group, although it was less in case of two-sided hernia in TEP group. An expression of pain syndrome was reliably lower in TEP group. CONCLUSIONS. Both methods demonstrated similar results and could be applied in treatment of inguinal hernias.